TYPES OF IMMUNE REACTION AT PATIENTS WITH ACUTE VIRAL HEPATITIS B - Lyadova, T.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
At patient with acute viral hepatitis B three types of immune reactions were established, determined by the character of answer of principal regulators cytokines: normally reactive, dissociative, and hyporeactive, which are found in close correlation with the severity degree of weight, clinical signs and outcomes of disease.  The got results allow to recommend the necessity of complex investigation of patients with acute viral hepatitis B with determination of markers of active viral replikation (DNA HBV) and level of principal regulators cytokine.